Growth performance of Woyto-Guji and Central Highland goat breeds under traditional management system in Ethiopia - Zergaw, N.; Dessie, Tadelle; Kebede, K. (2016)
The study was conducted to evaluate the productive and reproductive performance of Central Highland and Woyto-Guji goat breeds in Meta-Robi and Konso districts, respectively. A total of 240 farmers were interviewed using semi-structured questionnaires to describe kidding pattern, kidding interval, weaning age and milk production. On-farm performance traits were recorded on 730 goats of 157 households. In Konso, majority of kidding occurred in May, whereas in Meta-Robi it was in September. There was a difference in the average kidding interval and age at weaning between the breeds. Kids birth weight (2.03 Vs. 2.68kg) and does postpartum weight (26.6 Vs. 28.2kg) were lower in Woyto-Guji goats than in Central Highland goats. Average 90 day kids' weight and average daily weight gain between birth and 90 days were not different among the breeds. Average 180 day weight (15.7 Vs. 11.5kg) and average daily weight gain between 91 and 180 days (65.4 Vs. 31.9 g/day) were better in Central Highland goats than in Woyto-Guji goats.